DETERGENT AND DIATOM ANALYSIS IN SELAT AIR HITAM WATERS, KEPULAUAN MERANTI REGENCY, RIAU PROVINCE - Fuad, M Anwar; Nedi, Syahril; Siregar, Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research aims to analyze the detergent and diatom. content that has been implemented in April 2017. in the Selat Air Hitam Water, Kepulauan Meranti Regency. The method used in this research is survey. Analysis of detergent and Diatom content was done at the laboratoriumkimialaut and Diatom identification was performed at the laboratoriumbiologilaut. The results showed that the detergent content in the waters ranged from 0.5714 to 0.8095 mg /l. Diatom abundance based on laboratory test was 95,83 - 137,84 Ind /l and the relationship of detergent and diatom content in waters by using linear regressiony = 222,0 + - 156,9x with determination coefficientR2= 0,867 and correlation coefficient r = 0.9311. The relationship between detergent and diatom in the waters shows a very strong relationship. Keywords: Detergent, Diatom, Selat Air Hitam, Kepulauan Meranti.